Body mass index and incident cardiometabolic conditions in relation to obesity‐related cancer risk: A population‐based cohort study in Catalonia, Spain - Martina Recalde; Andrea Pistillo; Vivian Viallon; Emma Fontvieille; Talita Duarte‐Salles; Heinz Freisling (Cancer Medicine, 2023)
Abstract Background We investigated the association between body mass index (BMI) and obesity‐related cancer risk among individuals with/without incident hypertension (HTN), type 2 diabetes mellitus (T2DM), and cardiovascular disease (CVD) and the joint associations of overweight/obesity (BMI ≥25 kg/m2) and each cardiometabolic condition with obesity‐related cancer risk Methods We conducted a population‐based cohort (n = 1,774,904 individuals aged ≥40 years and free of cancer and cardiometabolic conditions at baseline) study between 2010 and 2018 with electronic health records from Spain. Our main outcome measures were hazard ratios (HRs) for incident obesity‐related cancers and relative excess risk due to interaction (RERI). Results A total of 38,082 individuals developed obesity‐related cancers after a median of 8 years of follow‐up. The positive association between BMI and obesity‐related cancer risk was similar among individuals free of cardiometabolic conditions (hazard ratio, HR per 5 kg/m2: 1.08, 95% confidence interval, CI: 1.06–1.10) and with incident HTN (1.05, 1.01–1.08). The association among those with incident T2DM was null (0.98, 0.93–1.03). There was a positive additive interaction between overweight/obesity and CVD (relative excess risk due to interaction [RERI]: 0.19 [0.09, 0.30]), meaning that the combined association was 0.19 more than the sum of the individual associations. In contrast, a RERI of −0.24 (−0.28, −0.20) was observed for the combined association between overweight/obesity and T2DM. Conclusions Public health strategies to reduce overweight can help prevent cancer cases among the general population and individuals with incident HTN/CVD. Further, weight‐loss interventions seem to lead to a greater cancer risk reduction among individuals with CVD.